205k views
5 votes
50 Points Each I know the answer: Solve by ELIMINATION

50 Points Each I know the answer: Solve by ELIMINATION-example-1

2 Answers

1 vote
  • 3x+y=-2
  • -3x+2y=14

Add both

  • 3y=12
  • y=4

put in first one

  • 3x+4=-2
  • 3x=-6
  • x=-2
User Shawntay
by
5.9k points
5 votes

Answer:

  • ( -2, 4)

Explanation:

We can see both equations have same variable 3x, one with positive and one with negative coefficient. If we add up the equations they will cancel, thus the variable x is eliminated.

Add up the equations and solve for y:

  • y + 3x + 2y - 3x = -2 + 14
  • 3y = 12
  • y = 12/3
  • y = 4

Now solve for x:

  • 4 + 3x = -2
  • 3x = -2 - 4
  • 3x = -6
  • x = -6/3
  • x = -2
User Vatsal Harde
by
5.2k points